Principle of Explosion Sequence

What is the basis for reason? And mathematics?

Moderators: AMod, iMod

Post Reply
Posts: 6220
Joined: Mon Mar 13, 2017 3:18 am

Principle of Explosion Sequence

Post by Eodnhoj7 »

All phenomena result from void voiding itself into form, with form voiding itself into many forms. Logically this sequence is a result of the Principle Explosion, where from contradiction anything results, empirically this sequence is a result of the Big Bang, where from nothingness everything results.

Expressed mathematically the sequence occurs from the divergence of 0 value points into the number line:


**** 1= .______. --->

**** -1= <--- .______.

(1-->1)--> (2, 1/2, -2, -1/2)

*** 2= .____.____. --->

*** 1/2 = .____. --->

*** -2 <--- .____.____.

*** -1/2 <--- .____.

(1-->2)--> (3, 1/3, -3, -1/3)

*** 3 .____.____.____. --->

*** 1/3 .____. --->

*** -3 <--- .____.____.____.

*** -1/3 <--- .____.

The line starts with point 0. This point zero projects to form the most basic quantifiable form: the line as 1 unit and -1 unit respectively (considering the line relativistically projects in both directions as one direction. The projection of 1 is the projection of -1 considering the line is relative in directions).

As the point projects again -2 and 2 results where -1/2 and 1/2 occurs simultaneously (this is considering 2 lines necessitates each line as 1/2 the original line).

The sequence continues as the line projects to another point as 3 and -3 and 1/3 and -1/3. For each projection of the point comes a projection of another line thus resulting in the number line as the projection of a point 0. All numbers, as x=x, originate with the projection of point 0 to another point 0 as (0 --> 0) and (0 <-- 0) as (0<-->0) or (0=0). The number line originates with 0.

Logically this sequence occurs from an empty assumption resulting in variables, thus mirroring its mathematical counterpart:

(• --> •) --> A, -A

(A-->A) --> (B, A/B, -A/B, -B)

(A-->B) --> (C, A/C, -A/C, -C)

Empirically this sequence occurs as:

"Nothing" therefore "Nothing" therefore "Cat" and "non-cat" (nothing negates itself into all variables as "non-cat" and the variable of A which can be just about anything in this case "cat")

(• --> •) --> A, -A

"Cat" therefore "Cat"


"Cat" therefore "Feline"


"Cat" therefore "Feline" therefore "wild"


"Cat" therefore "Feline" therefore "wild as Fraction of cat"


"Cat" therefore "feline" therefore "Not Wild" (ie cat may be something else rather than wild)

(A-->B)--> -C

"Cat" therefore "feline" is "not wild as fraction of cat" (ie cat may be domesticated)

(A-->B) ---> -A/C

This sequence results in being as composed of fractions and fractals where a modality is extension of the assertion it seeks to describe. The modality is part of the assertion. This reflects in all words used to describe said assertions. Words as tautologies are words as fractions.

For example:


(quality)--> (state) ---> (index) ---> (.......)
Post Reply